Impact of Internet companies on World Politics - E. S. Zinovyeva (Vestnik MGIMO-Universiteta)
The article analyzes the role of Internet companies in contemporary world politics. Large internetcompanies such as Facebook, Google etc., shape basic trends of the global information space thus influencing the environment of the world politics. Pivotal interests of internet companies lie in the commercial, but not political sphere, resulting in their indirect role as world political actors.